Augmented reality-based flat-sided building cards to improve students' understanding of mathematical concepts - Iwit Prihatin; Marhadi Saputro; Hartono Hartono (SAINTIS Publishing, 2022)
This study aims to improve students' understanding of mathematical concepts by applying augmented reality-based flat-sided wake-up cards media at SMP 10 Sungai Kakap. Experimental research with a quantitative approach was chosen as the method in this study. The instrument used was a description test in the form of pre-test and post-test with a population of 8th graders at SMP 10 Sungai Kakap, Kabupaten Kubu Raya, West Kalimantan which consisted of 2 classes. The research subjects were students of grade 8 B which consisted of 30 students who were selected by cluster random sampling. The data were analyzed using the paired data class t-test. The results showed that students' understanding of mathematical concepts increased after applying mathematics learning using augmented reality-based flat space card media.